Reconnection electric field estimates and dynamics of high-latitude boundaries during a substorm - Pitkänen, T.; Aikio, A. T.; Kozlovsky, A.; Amm, O. (Annales Geophysicae, 2009)
The dynamics of the polar cap and the auroral oval are examined in the evening sector during a substorm period on 25 November 2000 by using measurements of the EISCAT incoherent scatter radars, the north-south chain of the MIRACLE magnetometer network, and the Polar UV Imager. The location of the polar cap boundary (PCB) is estimated from electron temperature measurements by the mainland low-elevation EISCAT VHF radar and the 42 m antenna of the EISCAT Svalbard radar. A comparison to the poleward auroral emission (PAE) boundary by the Polar UV Imager shows that in this event the PAE boundary is typically located 0.7° of magnetic latitude poleward of the PCB by EISCAT. The convection reversal boundary (CRB) is determined from the 2-D plasma drift velocity extracted from the dual-beam VHF data. The CRB is located 0.5–1° equatorward of the PCB indicating the existence of viscous-driven antisunward convection on closed field lines. East-west equivalent electrojets are calculated from the MIRACLE magnetometer data by the 1-D upward continuation method. In the substorm growth phase, electrojets together with the polar cap boundary move gradually equatorwards. During the substorm expansion phase, the Harang discontinuity (HD) region expands to the MLT sector of EISCAT. In the recovery phase the PCB follows the poleward edge of the westward electrojet. The local ionospheric reconnection electric field is calculated by using the measured plasma velocities in the vicinity of the polar cap boundary. During the substorm growth phase, values between 0 and 10 mV/m are found. During the late expansion and recovery phase, the reconnection electric field has temporal variations with periods of 7–27 min and values from 0 to 40 mV/m. It is shown quantitatively, for the first time to our knowledge, that intensifications in the local reconnection electric field correlate with appearance of auroral poleward boundary intensifications (PBIs) in the same MLT sector. The results suggest that PBIs (typically 1.5 h MLT wide) are a consequence of temporarily enhanced longitudinally localized magnetic flux closure in the magnetotail.